Integrating Citizen Participation in the Development of New ICT Services for Smart Cities - Alexander Jesus Ricardo; Mónica Ayde Vallejo; José Edinson Aedo (Information)
The transition of cities towards a smarter approach significantly benefits from citizen participation in the development and implementation of innovative information and communication technology (ICT) products and services. Despite the emergence of various initiatives in recent years aimed at guiding the development of smart cities, there is still a lack of effective strategies to actively engage citizens, businesses, and educational institutions during the creation of these products and services. This study describes a set of practices that includes four co-creation techniques to facilitate the effort of software system development in collaboration with citizens and other stakeholders. The SEMAT standard is used to create and represent a method in which these practices are distributed across four stages: focus, definition, development, and validation. In each stage, a practice is proposed that incorporates a co-creation technique and complementary activities from various software engineering disciplines to promote active citizen participation; stimulate idea generation; and facilitate the creation of necessary documents and components for the development of the desired software system, including design systems, code files, conceptual representations, and technical diagrams, among others. Finally, the applicability and completeness of the method are validated through expert consultation in the fields of software engineering and smart cities. Recognized procedures are followed to obtain qualitative and quantitative results, such as improvement actions (addition or removal of elements), levels of consensus or acceptance, and opportunities for future work.